Recurrent pulmonary thromboembolism during radical cystectomy: A case report (Indian Journal of Case Reports, 2021)
Intraoperative incidences of pulmonary embolism (PE) have been reported in orthopedic and neurosurgeries. Here, we present the case of a 69-year-old man who presented with complaints of abdominal pain and hematuria for 2 months. He underwent radical cystectomy for urinary bladder cancer when he suddenly developed severe shock , hypoxia and decrease in lung compliance. We managed hypotension with vasopressors and inotropes guided by cardiac output monitoring. Post-operative CT pulmonary angiography revealed partially occluding thrombi in the left lower lobar pulmonary artery in segmental branches. The patient was started on therapeutic anticoagulation and he recovered subsequently. We commonly encounter thromboembolism in the post-operative period, and clinical presentation of massive occlusive embolus is well recognized. In this case, the presentation was intraoperative and the thrombus was non-massive, causing only partial obstruction of the pulmonary artery. This atypical presentation of intraoperative non-massive pulmonary thromboembolism needs to be recognized promptly. The use of invasive hemodynamic monitoring and point-of-care echocardiography is vital in the management of intraoperative pulmonary embolism.